2003
DOI: 10.1080/0007166031000085292
|View full text |Cite
|
Sign up to set email alerts
|

The effect of short-term fasting on performance traits and rectal temperature of broilers during the summer season

Abstract: 1. The present study was conducted to determine if detrimental effects of high temperature on broiler performance could be overcome by short-term fasting and to examine the effect of food withdrawal on the responses of two commercial strains (S1 and S2). 2. An experimental design was used with three feeding groups and two strains. Birds in the control (C) group were fed ad libitum during the experimental period (0 to 6 weeks), while feed was withdrawn in the other groups between 10:00 and 16:00 h during weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 22 publications
3
21
1
Order By: Relevance
“…Depending on the actual temperature endured by the chickens, the technique may have positive [10,5] or negative (present work) effects on growth and feed conversion. In general when the environmental conditions induce mortality (i.e., Ta > 33 °C for several hours during several consecutive days and Tb of some birds overpasses 44 °C, above which level survival is compromised) the feed withdrawal techniques show positive effects on overall performances.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the actual temperature endured by the chickens, the technique may have positive [10,5] or negative (present work) effects on growth and feed conversion. In general when the environmental conditions induce mortality (i.e., Ta > 33 °C for several hours during several consecutive days and Tb of some birds overpasses 44 °C, above which level survival is compromised) the feed withdrawal techniques show positive effects on overall performances.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic potential not only affects the growth response and body composition of the bird because of its effects on nutrient requirements (Havenstein et al 1993;Gous et al 1999) but also affects compensatory growth of broilers subjected to feed restriction (Yu et al 1990). Ozkan et al (2003) reported significant strain as well as strain | feeding regime interaction effects on body weight and weight gain when two strains were subject to short-term early feed restriction. Also, Rosa et al (2007) reported significantly better performance and carcass yield and lower abdominal fat deposition in AgRoss 308, a commercial line than PCLC, a non-improved line and a significant interaction between genetic group and dietary metabolizable energy level for feed conversion.…”
Section: Introductionmentioning
confidence: 95%
“…In poultry, temporary feed restriction before or during heat exposure is found to be an effective way to improve heat resistance by lowering metabolic heat production (Amand et al, 2004). In Turkey, Ozkan et al (2003) showed that feed withdrawal during the hottest period of the day reduced mortality without any negative effect on growth performance. Similar results were recently reported by De Basilio et al (2010).…”
Section: Strategies To Alleviate Heat Stress In Farm Animalsmentioning
confidence: 99%